2023
DOI: 10.1002/cjoc.202300576
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Deciphering the Mechanisms and Biological Functions of DNA Demethylation

Yang Feng,
Sheng‐Jun Chen,
Bi‐Feng Yuan

Abstract: Comprehensive Summary5‐Methylcytosine (5mC) is a dynamic and reversible epigenetic modification in genomic DNA of higher eukaryotes. It has been well‐established that the demethylation of 5mC occurs through the ten‐eleven translocation (TET)‐mediated oxidation of 5mC followed by thymine DNA glycosylase (TDG)‐initiated base excision repair (BER). Recent findings also have identified an alternative pathway of DNA demethylation. In this pathway, TET enzymes directly oxidize 5mC to form 5‐formylcytosine (5fC) or 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…The 10-11 translocation (TET) dioxygenases can sequentially oxidize 5mC to generate three modified forms of cytosine, 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC), and 5-carboxylcytosine (5caC). Thymine DNA glycosylase (TDG) plays a role in recognizing and removing 5fC and 5caC from the genomic DNA, which triggers a repair process known as base excision repair and leads to the restoration of unmodified cytosine. Although 5fC was initially discovered in mouse embryonic stem cells (mESCs), its abundance is lower compared to 5hmC and 5mC. , Aside from its role as an intermediate in DNA demethylation, 5fC has been found to influence the structure of the DNA double helix . It has also been suggested that 5fC and its oxidative counterpart, 5caC, can potentially serve as targets for specific reader proteins, implying that they may have regulatory functions in gene expression and chromatin organization. , …”
Section: Introductionmentioning
confidence: 99%
“…The 10-11 translocation (TET) dioxygenases can sequentially oxidize 5mC to generate three modified forms of cytosine, 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC), and 5-carboxylcytosine (5caC). Thymine DNA glycosylase (TDG) plays a role in recognizing and removing 5fC and 5caC from the genomic DNA, which triggers a repair process known as base excision repair and leads to the restoration of unmodified cytosine. Although 5fC was initially discovered in mouse embryonic stem cells (mESCs), its abundance is lower compared to 5hmC and 5mC. , Aside from its role as an intermediate in DNA demethylation, 5fC has been found to influence the structure of the DNA double helix . It has also been suggested that 5fC and its oxidative counterpart, 5caC, can potentially serve as targets for specific reader proteins, implying that they may have regulatory functions in gene expression and chromatin organization. , …”
Section: Introductionmentioning
confidence: 99%
“…6–9 5fC and 5caC can be converted back to unmodified cytosines through the base excision repair pathway or through direct deformylation or decarboxylation. 10–13 Despite being the two most prevalent DNA modifications, the biological functions of 5mC and 5hmC in DNA often have opposing effects, and abnormal DNA methylation or hydroxymethylation is closely linked to various diseases. 14–17…”
Section: Introductionmentioning
confidence: 99%